(untitled) (Research, Society and Development, 2020)
The present study aims to raise the possible weaknesses of the specifications of geriatric diapers in order to discriminate them in approved; approved with limitations and disapproved by the probability of risk of incidence and prevalence of skin lesions by pressure and/or moisture, according to the assumption that the quality of the components of geriatric diapers may play an important role in the appearance of skin lesions. We used an experience report, with a sample of four geriatric diapers, of the same package. They were used for testing: methylene blue, drinking water and graduated chalice. Scales were created for micition volume measurement and multicriteria model for the quality of geriatric diapers for hospital use. With the methodology of testing of industrial products and Multi Criteria Decision Aid (MCDA) it was possible to evaluate geriatric diapers according to the presence of varied levels of moisture, after the application of a test solution for simulation of voiding volumes. However, even without the weight on the geriatric diapers or with the application of only 1/4 of the weight specified in the package, the touch cover with volume from 400 ml, both the cover and the sheet, had different levels of presence of moisture. Thus, there is a probability of the association of the quality of geriatric diapers with the incidence and prevalence of pressure and/or moisture injury.